Finite Element Simulation of Frost Wedging in Ice Shelves. Issue 1 (December 2014) - Plate, Carolin; Müller, Ralf; Humbert, Angelika; Gross, Dietmar
Abstract Break‐up events in ice shelves have been studied extensively during the last years. One popular assumption links disintegration events to surface melting of the ice shelf in conjunction with growing melt‐water ponds, leading to hydro‐fracture. As this explanation only holds during warm seasons [1], the possibility of frost wedging as forcing mechanism for autumn and winter break‐up events is considered. Frost wedging can only occur if a closed ice lid seals the water inside the crack. Hence, the present study of frost wedging in a single crack uses ice lid thicknesses to evaluate the additional pressure on the crack faces. The investigation of the resulting stress intensity factor as a measure of crack criticality follows consequently. The results show that freezing water inside a crack can result in unstable crack growth of an initially stable water filled crack. (© 2014 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)